One size does not fit all: Group size and the late middle Pleistocene prehistoric archive. Issue 127 (February 2019) - Malinsky-Buller, Ariel; Hovers, Erella
Abstract: The role of demography is often suggested to be a key factor in both biological and cultural evolution. Recent research has shown that the linkage between population size and cultural evolution is not straightforward and emerges from the interplay of many demographic, economic, social and ecological variables. Formal modelling has yielded interesting insights into the complex relationship between population structure, intergroup connectedness, and magnitude and extent of population extinctions. Such studies have highlighted the importance of effective (as opposed to census) population size in transmission processes. At the same time, it remained unclear how such insights can be applied to material culture phenomena in the prehistoric record, especially for deeper prehistory. In this paper we approach the issue of population sizes during the time of the Lower to Middle Paleolithic transition through the proxy of regional trajectories of lithic technological change, identified in the archaeological records from Africa, the Levant, Southwestern and Northwestern Europe. Our discussion of the results takes into consideration the constraints inherent to the archaeological record of deep time – e.g., preservation bias, time-averaging and the incomplete nature of the archaeological record – and of extrapolation from discrete archaeological case studies to an evolutionary time scale. We suggest that technological trajectories of change over this transitional period reflect the robustness of transmission networks. Our results show differences in the pattern and rate of cultural transmission in these regions, from which we infer that information networks, and their underlying effective population sizes, also differed.